Hurricane Lilies, Lycoris Species, in Florida - Gary W. Knox (EDIS)
ENH-1036, a 3-page fact sheet by Gary W. Knox, describes the history and qualities of these bulbs that flower after heavy summer rains. Includes information on availability and descriptions of species that are widely available, and some less common species to look out for. Published by the UF Environmental Horticulture Department, May 2006.